Evaluating the impact of Physical Education on sedentary lifestyles in Indonesian students - Farid M. Alhumary; Tandiyo Rahayu; Andri Akhiruyanto; Said Junaidi; Heny Setyawati (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Sedentary behavior among Indonesian adolescents necessitates effective physical education to enhance health outcomes.